2015
DOI: 10.1016/j.nicl.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in fiber tractography predict neurodevelopmental outcomes in neonates with infantile Krabbe disease

Abstract: BackgroundKrabbe disease is a fatal neurodegenerative disease caused by rapid demyelination of the central and peripheral nervous systems. The only available treatment, unrelated umbilical cord blood transplantation, is effective only if performed before clinical symptoms appear. Phenotypic expressions of disease-causing mutations vary widely, but genotype–phenotype relationships are unclear. Therefore, we evaluated diffusion tensor imaging (DTI) tractography with volumetric analysis as a biomarker of early wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Correspondence can be achieved by sampling at equivalent levels along tracts ( Groeschel et al, 2014 , Verde et al, 2014 ) or parameterising WM tracts by arc length, essentially reducing entire tracts to a single, core line ( Corouge et al, 2006 , Goodlett et al, 2009 , O'Donnell et al, 2009 , Verde et al, 2014 , Yeatman et al, 2012 ). These methods have been used to study neurodevelopment in toddlers ( Geng et al, 2012 , Goodlett et al, 2009 ), WM heritability in twin neonates ( Lee et al, 2015 ), infantile Krabbe disease ( Gupta et al, 2015 ), and prenatal exposure to selective serotonin reuptake inhibitors ( Jha et al, 2016 ). However these methods are more suitable for tubular rather than sheet-like tracts.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondence can be achieved by sampling at equivalent levels along tracts ( Groeschel et al, 2014 , Verde et al, 2014 ) or parameterising WM tracts by arc length, essentially reducing entire tracts to a single, core line ( Corouge et al, 2006 , Goodlett et al, 2009 , O'Donnell et al, 2009 , Verde et al, 2014 , Yeatman et al, 2012 ). These methods have been used to study neurodevelopment in toddlers ( Geng et al, 2012 , Goodlett et al, 2009 ), WM heritability in twin neonates ( Lee et al, 2015 ), infantile Krabbe disease ( Gupta et al, 2015 ), and prenatal exposure to selective serotonin reuptake inhibitors ( Jha et al, 2016 ). However these methods are more suitable for tubular rather than sheet-like tracts.…”
Section: Introductionmentioning
confidence: 99%
“…A modest psychosine storage may affect murine neuronal and glial differentiation from NPCs (Castelvetri et al, 2011;Santambrogio et al, 2012;Teixeira et al, 2014) before overt toxicity mediated by storage overload (Hawkins-Salsbury et al, 2013;White et al, 2011) (Bongarzone et al, 2016;Ricca and Gritti, 2016). Interestingly, psychosine storage has been detected in the brain of GLD human foetuses (Igisu and Suzuki, 1984) and elevated psychosine blood concentration is considered a specific marker in infantile GLD patients (Escolar et al, 2017), who may display early white matter changes and functional disability (Gupta et al, 2015). The aggravated defects in neuronal/glial differentiation from human NPCs described here are in line with these clinical observations.…”
Section: Discussionmentioning
confidence: 99%
“…Interpreting MRI results from newborns is complicated because the degree of myelination is quite variable in this cohort. Gupta and coworkers () recently showed that diffusion tensor imaging (DTI) with quantitative tractography is an effective tool for evaluating infants with KD identified through NBS. However, this technique has not been tested on asymptomatic, at‐risk patients identified by NBS.…”
Section: Improvement Opportunitiesmentioning
confidence: 99%